The language of identity in Malaysian politics: Towards a theory of Malaysian political discourse - Halim, Rohizah (2011)
The use of language in political discourse is generally understood to perform the function of controlling and managing a group of people. But the language of politics can be understood to have more important purpose – even if it often operates below the level of conscious thoughts – that is, as a tool for the exercise of power.How does language fulfill this function? To understand, one has to look at the properties of language; words, phrases, sentences, meanings.In the end, political discourse creates a group with shared identity that in turn influence political beliefs and actions.To exercise their political power, politicians and leaders create a sense of shared identity through the channels and platforms made available to them. In studying the language used by politicians, Chilton (2004) proposes a set of 12 aspects of linguistic realizations in political discourse that can help to unravel the effect political language has on the creation of a political identity.This paper attempts to hold up these 12 aspects against seven collected speeches from the six Prime Ministers of Malaysia to see whether they can lead to conceptualizing a framework that can explain Malaysian political discourse.This framework could be utilized towards a study of political texts in a uniquely Malaysian context.